Media literacy versus fake news : critical thinking, resilience and civic engagement - MacDougall, Julian (Array, 2019)
This article shares research findings to support the case for media literacy education to facilitate resilient media engagement by young citizens. It shares the outcomes of a project funded by the US Embassy in London, which brought together leading researchers from the United States and UK with a range of key stakeholders, including journalists, teachers, students, librarians and information professionals. This ethnographic research consisted of interviews with prominent members of the stakeholder fields, four multi-stakeholder dialogic workshops and an extensive field review or literature, policy, pedagogic practice and existing educational resources. From the findings of this ethnography, the argument is presented that critical media literacy, if adopted as a mandatory subject in schools and taught as a dynamic literacy education, would better equip young citizens with resilience to ‘information disorder’ (Wardle and Derakhshan, 2017) than reactive resources (such as fact-checking and verification tools) and small-scale projects which focus primarily on competences.